2005
DOI: 10.1177/153537020523000907
|View full text |Cite
|
Sign up to set email alerts
|

Murine Macrophages Produce Endothelin-1 After Microbial Stimulation

Abstract: Endothelin-1 (ET-1) was originally characterized as a potent vasoconstrictor secreted by the endothelium and participating in the regulation of vascular tone. Subsequent analysis has revealed ET-1 to be a multifunctional peptide produced by a wide variety of cells and tissues under normal and pathologic conditions. The importance of macrophages as a source of ET-1 during infection and inflammation is supported by clinical observations in humans and in animal models of inflammation. We hypothesize that the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Besides basal vasoconstriction, they are known to exert mitogenic and anti-apoptotic actions [82,83] , as well as act as growth-promoting factors involved in embryonic and fetal development [84][85][86] . It has been reported that macrophages and monocytes act as a source of ET-1 production during infection and inflammation [87,88] . We have recently reported the expression of ET, especially ET-1 in AMC [89] .…”
Section: Nature Of Amcmentioning
confidence: 99%
“…Besides basal vasoconstriction, they are known to exert mitogenic and anti-apoptotic actions [82,83] , as well as act as growth-promoting factors involved in embryonic and fetal development [84][85][86] . It has been reported that macrophages and monocytes act as a source of ET-1 production during infection and inflammation [87,88] . We have recently reported the expression of ET, especially ET-1 in AMC [89] .…”
Section: Nature Of Amcmentioning
confidence: 99%
“…Alternative cleavage of big ET-1 by matrix metalloproteinase or chymase leads to production of extended-length isoforms, ET-1 and ET-1 , respectively (33,107). Although endothelial cells are considered the primary physiological source of vascular ET-1, it is now recognized that the vascular smooth muscle cells (VSMC), fibroblasts, and inflammatory cells (such as macrophages and leukocytes) are capable of ET-1 production under pathological conditions (28,45,50,52,88,101).…”
Section: Endothelin: Backgroundmentioning
confidence: 99%
“…TNF-α can provoke release of ET-1 from macrophages (11,12), and has been observed in combination with ET-1 to promote constriction in the coronary microvascular bed (44). During mental stress in patients with CAD, disinhibition of macrophages consequent to withdrawal of vagal efferent activity may thereby accelerate the production and release of ET-1 from macrophages and/or adjacent endothelial cells that secrete the peptide (17,45). Furthermore, Ach may affect the synthesis and release of ET-1 through action on endothelial cells, since it is known to stimulate the synthesis of NO and, in turn, NO inhibits the synthesis and release of ET-1 (46,47).…”
Section: A N G E R P a R A S Y M P A T H E T I C W I T H D R A W A mentioning
confidence: 99%